2011
DOI: 10.1007/s10157-011-0467-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling of the autosomal dominant polycystic kidney disease rat model

Abstract: We identified uremic retention solutes in ADPKD Cy/+ rats. Compounds related to ADPKD could be useful markers for detecting the early stage of ADPKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
4
14
0
Order By: Relevance
“…Importantly, our results are comparable with those of Taylor et al 14 . and Toyohara et al ., 15 who used metabolite profiling to investigate the cystic phenotype in jck mice and Cy/+ rats respectively, validating this approach as a means for identification of biomarkers of diagnostic and therapeutic potential.…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, our results are comparable with those of Taylor et al 14 . and Toyohara et al ., 15 who used metabolite profiling to investigate the cystic phenotype in jck mice and Cy/+ rats respectively, validating this approach as a means for identification of biomarkers of diagnostic and therapeutic potential.…”
Section: Discussionsupporting
confidence: 89%
“…CE‐MS‐based metabolomics studies revealed important findings in the various application areas as outlined in this review. For example, the use of this approach revealed γ‐glutamyl dipeptides as novel biomarkers for liver diseases , serum glycerol‐3‐phospate as a marker for predicting glucose intolerance , provided insight into the cytotoxic mechanism of seleno‐methionine and insight into the storage conditions of various foods .…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been used for various clinical metabolomics studies. For example, Toyohara et al used the CE‐MS approach of Soga (including use of a platinum sprayer needle) for comprehensive metabolic profiling of serum from an autosomal dominant polycystic kidney disease (ADPKD) rat model . In total 297 cationic and 190 anionic metabolites were detected in serum samples of this rat model and control rats, of which 21 cations and 19 anions accumulated significantly in the ADPKD rat model.…”
Section: Applicationsmentioning
confidence: 99%
“…In this study, using the CE-MS method [11,12,13,14,18], we comprehensively analyzed over 500 compounds and quantified 146 compounds (Supplementary Tables S1 and S2). We identified 25 compounds (6 anions and 19 cations) whose plasma concentrations were significantly changed by AST-120 treatment in 5/6Nx rats (the results are summarized in Figure 1 and Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive and quantitative analysis of charged metabolites by CE-MS was performed [12,13,14]. Plasma (50 μL) was immediately plunged into methanol (450 μL) containing internal standards (20 μM each of methionine sulfone (Wako, Osaka Japan) for cations, MES (Dojindo, Kumamoto, Japan) and CSA (D-Camphol-10-sulfonic acid, Wako).…”
Section: Methodsmentioning
confidence: 99%